ANALISIS FAKTOR KESELAMATAN DAN KESEHATAN KERJA (K3) DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DALAM MENINGKATKAN KESIAPAN OPERASIONAL PRAJURIT BATALYON INFANTERI 4 MARINIR - Ayun Wahyuni; Ary Kurniawan; Yuliantini Yuliantini (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
Battalion Infantery 4 Marines has the main task of carrying out combat tasks by searching for, approaching, and destroying the enemy with fire and movement or fending off enemy attacks with fire and close combat and counter attacks, in support of the main task of Battalion 4 Mar, operational readiness is very important for soldiers, one of which is the occupational safety and health (K3) of soldiers. In addition to the K3 factor of soldiers in improving the operational readiness of Battalion 4 March soldiers, soldiers are required to be qualified and professional individuals in carrying out their duties, soldiers must carry out their work selflessly called OCB. The purpose of this study was to examine the effect of occupational safety and health (K3) and OCB on the operational readiness of the soldiers Battalion Infantery 4 Marines. In this study using quantitative methods and for data processing in order to obtain results using the SPSS 25.0 application program. In determining the sample used, the researcher uses non-probability sampling with incidental sampling technique, to determine the number of samples using the Slovin the sample obtained is 239 respondents. The results in processing SPSS obtained results on the t- test. The t-count value for the K3 variable is 1.979 and the t-table obtained is 1.651, meaning that there is a positive and significant influence on the K3 variable on the operational readiness of soldiers and the t-value on the OCB variable is 1.858 with the t-table obtained is 1.651, meaning that there is a positive and negative effect. significant OCB variable on the operational readiness of soldiers. The data processing simultaneously with the f test. Ftable obtained is equal to 0.0513. Based on the results of the f test obtained at 1.233> 0.0513 and a significance value <0.05. So the conclusion is H0 is rejected and H1 is accepted. This shows that all independent variables (K3 and OCB) have a positive and significant effect on the Operational Readiness of the 4th Marine Infantry Battalion Soldiers. The value of the correlation coefficient (R) is 66.4%. It is in the strong category and the value of R2 = 0.441 which means that 44.1% of the Operational Readiness of the 4th Marine Infantry Battalion Soldiers can be explained by the K3 and OCB variables while the remaining 55.9% is influenced by other variables outside the model studied.